Pengembangan E-Book Fabel Nusantara Untuk Meningkatkan Kecepatan Membaca Pada Siswa Kelas V Sekolah Dasar - Dela Arwanda Dela Arwanda; Prana Dwija Iswara; Isrok’atun (Elementary Teacher Education Program, Majalengka University, 2023)
Learning to read is part of Indonesian language subjects, one of which is encouraging students to read quickly and find main ideas. This research aims to explore the use of Indonesian fable electronic books in learning to read. A research and development (R&D) approach was used in this research to assess product feasibility. This approach aims to do two things: (1) evaluate the product's efficacy in achieving goals; and (2) improve the product based on user and rater feedback. Methods and development start with material analysis, ideas, product improvements, conducting and revising product tests to validate the final product. This research was attended by twenty-five fifth grade students from one of the state elementary schools in Ogan Komering Ilir Regency, South Sumatra Province. Research findings show that the Fable Nusantar e-book is suitable for use as a teaching tool to improve the reading skills Learning to read is part of Indonesian language subjects, one of which is encouraging students to read quickly and find main ideas. This research aims to explore the use of Indonesian fable electronic books in learning to read. A research and development (R&D) approach was used in this research to assess product feasibility. This approach aims to do two things: (1) evaluate the product's efficacy in achieving goals; and (2) improve the product based on user and rater feedback. Methods and development start with material analysis, ideas, product improvements, conducting and revising product tests to validate the final product. This research was attended by twenty-five fifth grade students from one of the state elementary schools in Ogan Komering Ilir Regency, South Sumatra Province. Research findings show that the Fable Nusantar e-book is suitable for use as a teaching tool to improve the reading skills of fifth grade students as evidenced by the increase in reading speed on the learning outcomes obtained by students. of fifth grade students as evidenced by the increase in reading speed on the learning outcomes obtained by students.